Comparative study of vaginal delivery and caesarean section in antepartum eclampsia at tertiary care hospital - Kumari, Priti; Singh, Sipra; Khatun, Salma; Shashikar, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Eclampsia is characterized by the sudden onset of generalized tonic clonic seizures. Eclampsia is usually preceded by a history of the pre-eclampsia but rarely arises in a woman with minimally increased blood pressure and no proteinuria. Eclampsia most commonly occurs in the third trimester, though rarely eclampsia may occur before 20 wks in molar or multiple pregnancy. The aim of the study was to compare maternal and fetal outcome in antepartum eclampsia when terminated by vaginal delivery and caesarean section. Methods: 50 women with eclampsia attending emergency department OBG department of Katihar Medical College, Katihar were collected from Feb 2015 to Sep 2016. Depending upon the mode of delivery, they were divided into two groups, CD group where caesarean section was performed and VD group where vaginal delivery was performed. Results: Of the 50 cases, caesarean section was done in 40% of the cases, while vaginal delivery was carried was carried in 60%.Maternal complications in CD group was 35% and 80% in VD group (p<0.001).The incidence of live births, still birth and neonatal death was 85%, 15%, 0% in CD group and 60%, 40%, 10% in VD group. The corrected perinatal mortality was 50%. Conclusions: Timely caesarean section reduces maternal and perinatal mortality and improves their outcome in antepartum eclampsia.